2002
DOI: 10.1053/jlts.2002.36394
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous radiofrequency thermal ablation of hepatocellular carcinoma: A safe and effective bridge to liver transplantation

Abstract: The incidence of hepatocellular carcinoma (HCC) is increasing in the United States. Although liver transplantation is an effective means of treating selected patients, pretransplantation tumor progression may preclude some patients from undergoing transplantation. The aim of this study is to determine the safety and efficacy of percutaneous radiofrequency thermal ablation (RFA) in 33 consecutive patients with nonresectable HCC and advanced cirrhosis. Mean subject age was 57.2 ± 10.6 years, mean Child‐Turcotte‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
116
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(124 citation statements)
references
References 43 publications
6
116
0
2
Order By: Relevance
“…Explant-based evaluation of RFA found in the literature have been few, small in scale, and in disagreement regarding complete necrosis rates (ranging from 21% to 75%). 22,39,46 Most recently, a larger study of 50 explants showed 55% (63% for tumors Յ3 cm) complete response rate after RFA treatment prospectively limited to a single session. 26 Our result, obtained after multiple-session treatments as needed, is not inconsistent with this finding and, we believe, reflects a local efficacy that can be realistically expected with meticulous technique 47 and close posttreatment surveillance, both of which are crucial for optimizing outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Explant-based evaluation of RFA found in the literature have been few, small in scale, and in disagreement regarding complete necrosis rates (ranging from 21% to 75%). 22,39,46 Most recently, a larger study of 50 explants showed 55% (63% for tumors Յ3 cm) complete response rate after RFA treatment prospectively limited to a single session. 26 Our result, obtained after multiple-session treatments as needed, is not inconsistent with this finding and, we believe, reflects a local efficacy that can be realistically expected with meticulous technique 47 and close posttreatment surveillance, both of which are crucial for optimizing outcome.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Recently in the United States and abroad, however, RFA has emerged as the first-line treatment for small, nonresectable cases of HCC, such as those fulfilling transplant criteria, with TACE filling a secondary role or reserved for more extensive disease. [16][17][18][19][20][21] Therefore, a potentially beneficial role of RFA while awaiting OLT has been widely discussed, [22][23][24][25][26] although it remains unsubstantiated. The present study was undertaken to assess the efficacy of RFA as a bridge to liver transplantation.…”
mentioning
confidence: 99%
“…Several investigators have reported that percutaneous RF ablation for patients with small HCC nodules provides favorable survival with excellent local control, 15,16 and it may also be used as a bridge to liver transplantation. 17,18 The RF current emitted from the electrode is converted into heat and necrotizes the tumor. Therapeutic efficacy is considered to be more predictable with RF ablation than with PEIT, as the latter depends on diffusion of liquid ethanol in tissue.…”
mentioning
confidence: 99%
“…In our study, the detection of RFA incomplete response by means of computed tomography scan had a 50% sensitivity and 100% specificity. The reported rates of complete pathological response in other works were variable but lower than those reported by N' Kontchou et al: 20%,3 34.2%, 4 37.5%, 5 46.7%, 6 55%, 7 70.3%, 8 and 75%. 9 In these studies, as in ours, pathological examination was performed using hematoxylin-eosin stains.…”
mentioning
confidence: 58%